2016
DOI: 10.1007/s10800-016-1024-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic oxidation of urea on a sintered Ni–Pt electrode

Abstract: Urea is present in the environment as a result of large amounts of wastewater from various origins. One of the most effective methods for disposing of urea involves electrochemical oxidation. This study investigated the use of sintered Ni-Pt electrodes as anodes in the electrocatalytic oxidation of urea. The activity of the Ni-Pt electrodes was compared with those of conventional Ti/Pt and Ni electrodes. Based on our results, the sintered Ni-Pt electrodes exhibited much higher activity in the oxidation of urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Microbial-based electrochemical systems show promise, but they involve complex bacterial cultivation, long start-up times, and stringent working conditions . With the advent of nanotechnology, inorganic catalysts have emerged as favorable electrode candidates for urea electro-oxidation. Noble metals (e.g., Pt, Rh, Ru, and Ir) were the focus of many early reports, ,, , but full-scale application is limited by their high cost and low abundance. Recent advances in earth-abundant catalyst development have shown that nickel, which is also the active metal in the urease enzyme, is a good alternative to noble metals. ,,,,, While promising, nickel still suffers from limitations including a high over-potential requirement (∼1 V) ,,, and catalyst deactivation by urea oxidation byproducts. …”
Section: Introductionmentioning
confidence: 99%
“…Microbial-based electrochemical systems show promise, but they involve complex bacterial cultivation, long start-up times, and stringent working conditions . With the advent of nanotechnology, inorganic catalysts have emerged as favorable electrode candidates for urea electro-oxidation. Noble metals (e.g., Pt, Rh, Ru, and Ir) were the focus of many early reports, ,, , but full-scale application is limited by their high cost and low abundance. Recent advances in earth-abundant catalyst development have shown that nickel, which is also the active metal in the urease enzyme, is a good alternative to noble metals. ,,,,, While promising, nickel still suffers from limitations including a high over-potential requirement (∼1 V) ,,, and catalyst deactivation by urea oxidation byproducts. …”
Section: Introductionmentioning
confidence: 99%
“…Highly efficient catalysts are thus required to accelerate the reaction kinetics, and multifarious catalysts have been developed. [21][22][23][24][25][26][27][28][29] Among them, noble metals are restricted by their high cost, and attention has been directed to nickel-based materials that have low cost but promising electrocatalytic activity. [30][31][32] Please note that electrocatalytic reactions occur at the interface of reactants and catalysts, which involve the process of adsorption, activation, and desorption.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to enhancing electrical conductivity and structure stability catalytic activity, sensitivity, and durability. [14] Therefore, Several nickel-based binary materials were used as catalysts for urea electrooxidation (UEO), like NiÀ Cu, NiÀ Bi, [15] NiÀ Co, [16] NiÀ Cr, [17] NiÀ Pt, [18] and NiÀ Pd. [19] Binary transition metal oxides such as Mn/Ni, which provide multiple oxidation states to facilitate the oxidation reaction, significantly improve the intrinsic conductivity and electrochemical activity compared with their monometallic oxide counterparts.…”
Section: Introductionmentioning
confidence: 99%